Electrochemical Characterization of Pre‐conditioning Process of Electrospun Nanofiber Electrodes in Polymer Electrolyte Fuel Cells1. Issue 5 (19th July 2018) - Si, D.; Zhang, S.; Huang, J.; Wang, C.; Liu, Y.; Zhang, J.
Abstract: Structure innovation and optimization of polymer electrolyte fuel cell (PEFC) catalyst layers is instrumental in improving catalyst utilization and effectiveness. Electrospinning technique has been recently used to fabricate nanofiber electrodes for PEFCs with improved performance compared to electrosprayed electrodes. However, the origins for the performance improvement are yet poorly understood. This study examined the evolution of the electrochemically active surface area (ECSA) and electrochemical impedance spectroscopy (EIS) during the pre‐conditioning process, and compared the performance of electrospun nanofiber electrodes with electrosprayed electrodes within a wide range of operating conditions. ECSA increases, and both mass transfer resistance and charge transfer resistance decrease monotonically during the pre‐conditioning process of electrospun nanofiber electrodes. Such effects are attributed to the dissolution of poly(acrylic acid) (PAA) and the ensuing change of the interface between Pt and the ionomer. After pre‐conditioning, the electrospun nanofiber electrodes outperformed the electrosprayed electrodes with the same Pt‐loadings at 80 °C, whereas the electrosprayed electrodes have higher cell voltages at high current densities at 60 °C and 70 °C in high relative humidity (RH) range. The change in the relative performance of the two types of electrodes is attributed to the competing effects of electrode thickness and pore sizes on cathode gas transport.